Construction and characterization of an infectious cDNA clone of turtle grass virus X from a naturally infected Thalassia testudinum plant - Luis Alvarado-Marchena; Bradley T. Furman; Mya Breitbart (mBio)
ABSTRACT Seagrasses are a polyphyletic group of marine flowering plants that play crucial roles in nearshore ecology, yet their interactions with viruses remain largely unexplored. This study presents the construction and characterization of an infectious cDNA clone of the potexvirus turtle grass virus X (TGVX). The complete genome of this positive-sense single-stranded RNA virus was amplified from field samples of Thalassia testudinum and assembled into a pLX-based mini binary vector using a multi-fragment directional cloning strategy, resulting in the infectious clone pLX-TGVX. Agroinfection assays of potexvirus-free T. testudinum plants resulted in systemic infections by TGVX, as confirmed by multiplex RT-PCR experiments and phenotypic changes reflecting virus-induced symptoms. Ultrastructural studies also demonstrated significant cytopathological changes resulting from TGVX infection, including chloroplast swelling, reduced thylakoid grana, and the presence of viral replication organelles and filamentous virus-like particles. The development of the TGVX infectious clone offers a novel tool for investigating the impact of this virus on seagrass health and productivity. This study demonstrates the first successful agroinfection of a marine plant with an infectious clone, creating a new avenue for studying viruses identified through sequence-based surveys and paving the way for exploring the ecological significance of viral infection in these critical marine ecosystems.IMPORTANCEThis study pioneers the construction of an infectious clone of turtle grass virus X and describes its application in the natural marine plant host, Thalassia testudinum. The creation of this infectious clone not only provides a valuable tool for marine plant virology research but also opens new avenues for exploring the influence of viral infections on the health and productivity of seagrass meadows. Given that seagrasses play a crucial role in sediment stabilization, nutrient cycling, and habitat provisioning, understanding the impact of viruses on these ecosystems is essential for their effective conservation and management. This methodological advance enables detailed studies of viral replication, virus-host interactions, and the broader ecological implications of viral infections in marine plants.